Chapter 5.32 The Profession of Research Management and Administration in Iceland - Gréta Björk Kristjánsdóttir; Úlfar Kristinn Gíslason; Ásta Sif Erlingsdóttir (Emerald Publishing Limited, 2023)
Research management is slowly being recognised as a profession in Iceland as demands from funders and quality assurance have increased. The Icelandic research community is very small and funding for research is limited. The development of the profession in Iceland is tightly connected to international cooperation in research and participation in international programmes, in particular, the EU framework programmes. This participation has increased the administrative burden on researchers and shown the need for a specific profession that manages all other aspects of the research enterprise. This has slowly developed from being mostly financial management of grants into complete research management from idea to impact. A pivotal moment for research management in Iceland was the founding of ICEARMA in 2012, which has put a spotlight on the role of research managers within institutions, and led to most major research institutions hiring a designated research manager. This has also increased cooperation within the community.
10.1108/978-1-80382-701-820231066; 10.1108/978-1-80382-701-820231066; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262